ANALISIS STRATEGI PEMASARAN MENGGUNAKAN MATRIKS IE DAN MATRIKS SWOT (STUDI KAUSUS: MARCO DONUTS COFFE & RESTO, GALAXY) - Khotaman, Annisa Nabila; Farros, Fadhl Faishol; Hidyatullah Sudrajat, Muhammad Fauzi Nur; Geraldy, Rizky; ma'ruf, Shofa Mujahidah (Journal for Management Student (JFMS), 2023)
Marco Donuts Coffee and Galaxy Resto is a type of business in the culinary field that was established in 2021. Marco Donuts Coffee and Resto Galaxy must meet consumer needs every day and determine the right sales strategy to be able to compete with businesses in other culinary fields. The purpose of this study is to analyze internal factors and external factors that influence the number of visitors who come to Marco Donuts Coffee and Resto Galaxy, develop appropriate alternative strategy designs and provide recommendations for alternative strategies that can be used by Marco Donuts Coffee and Resto Galaxy according to internal and external conditions. . Data analysis used the IE and SWOT methods using two stages of data analysis implementation. The results of this study are that the Marco Donuts Coffee & Resto Galaxy IFE matrix produces an average IFE value of 2.56 and an average EFE of 3.24. The cafe's position is in quadrant II which gives an indication that the cafe is currently in a growth position and the building strategies implemented by managers are intensive and integrative strategies, intensive strategies include market penetration, market development and product development. While the integrative strategy includes forward and backward integration. From these results, it is hoped that in the future the cafe will be able to increase their strengths and improve the deficiencies that we have received, so that consumers can be better and gain the trust of the public in Marco Donuts Coffee & Resto Galaxy.